Surface-initiated RAFT polymerization from vapor-based polymer coatings. (15th August 2018) - Venkidasubramonian, Gowthamy; Kratzer, Domenic; Trouillet, Vanessa; Zydziak, Nicolas; Franzreb, Matthias; Barner, Leonie; Lahann, Joerg
Abstract: Surface-initiated reversible addition-fragmentation chain transfer (SI-RAFT) polymerization was used to synthesize poly(methyl methacrylate) (PMMA) and poly[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammoniumhydroxide (PMEDSAH) brushes grafted from reactive poly[ p- xylylene] surfaces. The synthetic approach involved functionalization of substrates via chemical vapor deposition polymerization of an electron-deficient alkynyl-functionalized [2.2]paracyclophane derivative. An azide-functionalized RAFT agent was anchored to the resulting poly[( p -xylylene-4-methyl propiolate)-co- p -xylylene] films via copper-free click-chemistry. Subsequent SI-RAFT polymerization yielded PMMA and PMEDSAH films with narrow dispersity which was further tuned by varying the concentration of a sacrificial RAFT agent in solution. Polymer dispersity was determined by size exclusion chromatography to be in the range of 1.2–1.4 for both polymers. This work provides a novel surface modification strategy to decorate a wide range of different substrates with polymer brushes, thereby eliminating the need for cumbersome modification protocols, which so far had to be established for each substrate material independently. Graphical abstract: Image 1 Highlights: Novel approach for SI-RAFT polymerization strategy applicable to a range of organic and inorganic surfaces. Vapor-based reactive coatings based on functionalized poly- p- xylylene for SI-RAFT polymerization. The surface modification strategy can be extended to the synthesis of a variety of polymers.